Dempster Shafer Untuk Sistem Diagnosa Gejala Penyakit Kulit Pada Kucing - Widyaningsih, Maura; Gunadi, Rio (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
Expert System which is a branch of Artifical Intelligence, who learned about the estimation or decision-making ability of an expert. Methods and concepts are still needed in solving the problem of diagnosis, with engineering calculations involve computing systems., given the level of need for information and resolving cases. The application development is aimed at implementing the knowledge of an expert into a program that can help in diagnosing the symptoms of skin health problems in cats. Dempster Shafer (DS) is a method that is non monotonous in solving the problem of uncertainty due to the addition or subtraction of new facts.The system is made to diagnose the type of skin disease in cats after applying the method of DS. The system can also perform data management if there is a data change disease, symptoms, treatment solutions, as well as the rules of the disease. The diagnosis system with DS according to analysis from experts.